Emergence of new variants of antibiotic resistance genomic islands among multidrug‐resistant Salmonella enterica in poultry - Emiliano Cohen; Maya Davidovich; Assaf Rokney; Lea Valinsky; Galia Rahav; Ohad Gal‐Mor (Environmental Microbiology, 2020)
Summary Non‐typhoidal Salmonella enterica (NTS) are diverse and important bacterial pathogens consisting of more than 2600 different serovars, with varying host‐specificity. Here, we characterized the poultry‐associated serovars in Israel, analysed their resistome and illuminated the molecular mechanisms underlying common multidrug resistance (MDR) patterns. We show that at least four serovars including Infantis, Muenchen, Newport and Virchow present a strong epidemiological association between their temporal trends in poultry and humans. Worrisomely, 60% from all of the poultry isolates tested ( n = 188) were multidrug resistant, mediated by chromosomal SNPs and different mobile genetics elements. A novel streptomycin‐azithromycin resistance island and previously uncharacterized versions of the mobilized Salmonella genomic island 1 (SGI1) were identified and characterized in S . Blockley and S . Kentucky isolates respectively. Moreover, we demonstrate that the acquisition of SGI1 does not impose fitness cost during growth under nutrient‐limited conditions or in the context of Salmonella infection in the mouse model. Overall, our data emphasize the role of the poultry production as a pool of specific epidemic MDR strains and autonomous genetic elements, which confer resistance to heavy metals and medically relevant antibiotics. These are likely to disseminate to humans via the food chain and fuel the increasing global antibiotic resistance crisis.

Detection of Erwinia herbicola pv. gypsophilae in gypsophila plants by PCR - Shulamit Manulis; Nina Kogan; Lea Valinsky; Orit Dror; Frida Kleitman (European Journal of Plant Pathology, 1998)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)